Efeito da melatonina na proteção contra estresse oxidativo induzido em células eritróides K562 - Paula, Carla Peres de (2020)
Erythrocytes are anucleated cells that play an extremely important role, since they participate in the transport of oxygen (O2) to tissues. Changes in the structure or functioning of the erythrocyte can lead to several deficiencies, such as hemolytic anemias, as the main clinical causes that can lead to an increase in the production of Reactive Oxygen Species (ROS), aggravating the patient's clinical condition. Several compounds have been studied as complementary therapy in hemolytic anemias to end the oxidative effects caused by these diseases, but no success has been allowed until then. Melatonin is a hormone that participates as a regulator of the sleep cycle, and more recently a role as an antioxidant has also been given to this compound. In this context, the present study aimed to evaluate the direct and indirect antioxidant effects of melatonin on erythrocyte cells, using K562 erythroid cells as a biological model. Therefore, a genetic expression and protein content of different antioxidant enzymes is available in K562 cells, differentiated or not by the addition of hydroxyurea and hemin in the face of melatonin treatment (1nM and 1mM) when induced or without oxidative stress (100μM H2O2). Viability, differentiation and level of lipid peroxidation are also available in these cells. Our results show that the administration of 1nM melatonin leads to an increase in the amount of undifferentiated K562 cells when exposed to oxidative stress induced by H2O2, in addition to decreasing the levels of lipid peroxidation in these cells. mRNA expression of the antioxidant enzymes PRDX1 and PRDX2 was increased when 1mM melatonin was administered in the presence of H2O2 in differentiated cells (PRDX1 mRNA - 50% on day 2 and 50% on day 4; PRDX2 mRNA - 100% on day 2 and 66% on day 4). An analysis of the protein content also showed important effects of melatonin, whose administration of 1mM increased the expression of NRF2 (290% without H2O2, and 437% with H2O2) and of the antioxidant enzymes PRDX2 (20% without H2O2 and 57% with H2O2) and CAT (170% without H2O2 and 200% with H2O2) in differentiated cells on day 4. In this context, a melatonin has shown a promising therapeutic agent in this type of cell, modifying an expression of important biomarkers related to erythrocyte redox metabolism and showing itself potentially important for new antioxidant therapies.